Karakteristik Sensori dan Kesukaan Konsumen pada Gnocchi Chips: Proporsi Kentang-Talas dengan Penambahan Ikan Bandeng - Rahma Aliyah Nurul Fadilah; Any Sutiadiningsih; Ila Huda P. Dewi; Qorry' Aina (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study aimed to determine the sensory characteristics, consumer acceptance level, and the best formulation of gnocchi chips with different potato–taro proportions and the addition of milkfish. The research employed a quantitative method with an experimental approach. The experiment was conducted in two stages. The first stage involved the selection of potato and taro proportions using three formulations, namely 40%:60%, 30%:70%, and 20%:80%, to determine the best formulation. The selected potato–taro proportion was then used in the second stage, which involved the addition of milkfish with three formulations, namely 23%, 30%, and 37%. Data from the first stage were analyzed using the Friedman test, while data from the second stage were analyzed using One-Way ANOVA. The results showed that the addition of milkfish significantly affected the sensory characteristics of gnocchi chips. The best formulation was obtained from the combination of 20% potato and 80% taro with 30% milkfish addition, which was categorized as “liked” by consumers. This formulation produced sensory characteristics including a dark golden-brown color, a strong and balanced aroma of tubers and milkfish, a crispy yet slightly hard texture, and a savory taste with a balanced combination of tuber and milkfish flavors.